Analisis Kuat Tekan Beton dengan Penambahan Tras dan Pengembangan Panduan Praktikum Beton - Rahmat Saliko; Fadly Achmad; Aryati Alitu (Transbahasa, 2025)
Concrete is a versatile construction material that has had a major impact on global reconstruction. This is because concrete is an important element in the formation of structures, due to its high compressive strength. This study aims to analyze the effect of adding trass to the compressive strength of concrete as a filler. The variations in trass addition were 5%, 10%, 15%, and 20%. In addition, this study also produced a product in the form of a practical guide for concrete construction based on fillers. The method used was laboratory testing with a concrete compression testing machine to determine the strength characteristics of each percentage Concrete mix. The materials used include cement, coarse aggregate, fine aggregate, from PT. HPP HARMONIS Telaga Biru, and the trass used is Lompoto'o trass, Central Suwawa. The testing was carried out at the Civil Engineering Laboratory of Gorontalo State University. The results of the study showed that concrete with 0% trass had a strength of 25.93 MPa, 5% trass had a strength of 27.51 MPa, 10% trass had a strength of 24.37 MPa, 15% trass had a strength of 22.55 MPa, and 20% trass had a strength of 21.48 MPa. The conclusion is that the addition of trass will increase the strength of concrete at a certain percentage, and the effect of using trass in concrete as an additive causes an increase in the volume weight of concrete. In addition, the validity results of the developed guidelines showed a value of 83.4%, which falls into the good category, so it can be said to be effective in supporting concrete practical activities or concrete with trass additives.